Four new lead(ii)–iridium(iii) heterobimetallic coordination frameworks: synthesis, structures, luminescence and oxygen-sensing properties1. Issue 10 (14th March 2015) - Chen, Yi-Ting; Lin, Chun-Yen; Lee, Gene-Hsiang; Ho, Mei-Lin
<x xml:space="preserve">Abstract</x> Crystalline lead(ii)–iridium(iii) heterobimetallic coordination frameworks were prepared and characterized, and one was mixed with C480 to form a ratiometric oxygen sensor for the determination of oxygen in real gas.